2018
DOI: 10.1007/s10489-018-1357-1
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous and connected intersection crossing traffic management using discrete-time occupancies trajectory

Abstract: In this paper, we address a problem of safe and efficient intersection crossing traffic management of autonomous and connected ground traffic. Toward this objective, we propose an algorithm that is called the Discrete-time occupancies trajectory based Intersection traffic Coordination Algorithm (DICA). We first prove that the basic DICA is deadlock free and also starvation free. Then, we show that the basic DICA has a computational complexity of O(n 2 L 3 m ) where n is the number of vehicles granted to cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…e data analysis results in Table 1 further indicate that the correlation between the jerk e ect and driving behavior increases by 50.6% on average compared to that of an RV since V2V communication technology provides instant information regarding the interactions between vehicles [33,36,37]. is nding may improve the stability of connected tra c ow.…”
Section: Data Mining Analysismentioning
confidence: 97%
“…e data analysis results in Table 1 further indicate that the correlation between the jerk e ect and driving behavior increases by 50.6% on average compared to that of an RV since V2V communication technology provides instant information regarding the interactions between vehicles [33,36,37]. is nding may improve the stability of connected tra c ow.…”
Section: Data Mining Analysismentioning
confidence: 97%
“…Other methods proposed in the previous studies [6][7][8][9] do not discretize the intersection. In Yan et al's study, 6 they identified the compatible trajectories of the vehicles in the intersection which are the trajectories that are not in conflict with each other.…”
Section: Related Workmentioning
confidence: 99%
“…The vehicles communicate with each other to broadcast their upcoming entrances into the intersection, and the scheme has set of rules to be followed by the vehicles in case the vehicles have conflicting trajectories in the intersection. In Lu and Kim's paper, 9 instead of discretizing the intersection, the vehicle's actual occupancy is used. The motivation of Lu and Kim 9 is to overcome the increase in computational complexity of the reservation-based scheduling when the granularity of cells is high.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…With the increasing penetration of PV, the large deviations of the PV output power result in a series problem such as voltage deviation, frequency oscillation, even unplanned islanding. Based on this [30]- [34], the proposed CNN based image regression model is focusing on building a relationship between the input cloudy sky images and the solar irradiations. Recently, the CNN based image processing, especially for image classification, is developing very fast.…”
Section: Introductionmentioning
confidence: 99%